The Role of Constructivism in Modern Educational Philosophy: A Comparative Analysis - Amie Primarni; Ardit Hoxha; Rashad Rzayev (International Journal of Educational Narratives, 2024)
Abstract Background: Constructivism has been a foundational theory in modern educational philosophy, emphasizing the role of the learner in constructing knowledge through experience and interaction with their environment. This pedagogical approach contrasts with traditional methods that prioritize rote learning and teacher-centered instruction. As educational systems evolve to meet the demands of the 21st century, understanding the role of constructivism in shaping contemporary educational practices becomes crucial. Objective: This study aims to compare the role of constructivism in modern educational philosophy by analyzing its impact across different educational settings. Specifically, the research examines how constructivist principles are integrated into various teaching strategies and how they influence student learning outcomes in comparison to traditional approaches. Method: A qualitative comparative analysis was conducted, involving a review of existing literature and case studies from different educational institutions. Data was gathered from research articles, educational reports, and interviews with educators who implement constructivist methodologies. The study also compared case examples from countries with varying educational systems to explore the global application of constructivism. Results: The study found that constructivist teaching strategies significantly improve critical thinking, problem-solving, and collaborative learning skills among students. Schools that implemented constructivist approaches reported higher student engagement and greater long-term retention of knowledge. In contrast, traditional methods were more effective for rote memorization but less conducive to developing higher-order thinking skills. Conclusion: Constructivism plays a pivotal role in modern educational philosophy, promoting active learning and student-centered education. The findings suggest that constructivist approaches are more aligned with the demands of the contemporary workforce and help prepare students for complex real-world challenges.